FAKTOR-FAKTOR YANG MEMPENGARUHI PENATAUSAHAAN BARANG MILIK DAERAH DI KABUPATEN YAHUKIMO - Riswanjaya Tandibiring; Paulus K. Allo Layuk; Anthonius H. Citra Wijaya (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
This study aims to identify determinants in managing the goods for local government in Yahukimo regency. The research question designed was what were the determinants of the goods for local government management? The aspects in this research comprised of; 1) bookkeeping, inventory and reporting which were based on registration process of the goods for local government; and 2) the recording that is based on category and codification of the goods for local government. The management of goods for local government is mandated under the Regulation of Ministry of Home Affairs no. 17 in 2007 titled Technical Management of The Goods for Regional/Local Governments. According to this regulation, the goods for local government management is defined as assets management activities that are consist of bookkeeping, inventory and reporting for goods of local governments in Indonesia. A qualitative research method was applied to obtain descriptive data. An in-depth interview technique was used to collect qualitative data through interviewing key informants. The key informants were selected based on their major involvement in managing goods of the local governments in 5 local agency units in Yahukimo regency. The 5 local agencies were from Forestry, Health, Agriculture, Fishery and Plantation Service, the Regional Secretariat and Financial and Assets Management Agency in Yahukimo Regency. The results of this research revealed that the management of goods for local government in Yahukimo regency was ineffective as mandated by the Regulation of Ministry of Home Affairs no. 17 in 2007. There were some factors of which determining this ineffectiveness. The limitations of human resources in terms of the qualities as well as quantities, the constraints of budget for the goods management, and low coordination within local government agencies were some of the identified caused of the ineffectiveness. From the inventory management context, the causes of ineffectiveness were the low number of staff for inventory, the unavailability of costs for inventory and the low skillful treasurers for government goods. Meanwhile, the reasons of low goods management reporting were the absence of punishments and rewards systems, the low human resources capacities in regards with government goods treasurers, and low commitments from managers of the local government regarding trainings to empower their staff. Key words: management of goods for local government, Yahukimo regency